Highly Oxygen Non-Stoichiometric BaSc0.25Co0.75O3-das a High-Performance Cathode for Intermediate-Temperature Solid Oxide Fuel Cells - Liu, B.; Sunarso, J.; Zhang, Y.; Yang, G.; Zhou, W.; Shao, Zongping (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2018)
© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim. Lowering the operating temperature of solid oxide fuel cells (SOFCs) is highly desirable to reduce the cost and increase the lifetime, which relies upon the development of a cathode component with high oxygen reduction reaction (ORR) activity at a lower temperature. Herein, we report the characterization of high-performance BaSc x Co 1-x O 3-d (x=0, 0.125, 0.25, and 0.375) perovskite SOFC cathodes. Unlike BaCoO 3-d , which adopts 2H-hexagonal perovskite structure, the replacement of 25mol% of Co with Sc stabilizes the cubic structure, which also leads to the significant reduction in area specific resistances and their activation energies between 650 and 500°C (for BaSc 0.25 Co 0.75 O 3-d ) relative to the non-doped BaCoO 3-d . In this temperature range, BaSc 0.25 Co 0.75 O 3-d displayed a remarkably high ORR activity compared to Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-d (BSCF), the current cathode benchmark. We attribute such superior ORR performance to the higher oxygen non-stoichiometries of BaSc 0.25 Co 0.75 O 3-d relative to BSCF, which also translates to the higher oxygen bulk diffusion and surface exchange coefficients for the former compared to the latter. As a result, a single fuel cell based on an anode-supported 20µm thick samarium-doped ceria electrolyte and BaSc 0.25 Co 0.75 O 3-d cathode achieved a very high peak power density of 1723mWcm -2 at 650°C. We also demonstrated the possibility to increase the ORR activity of the BaSc 0.25 Co 0.75 O 3-d cathode by impregnation of a low amount of silver.